Co(OH)2@FeCo2O4 as electrode material for high performance faradaic supercapacitor application. (10th March 2019) - Wang, Zidong; Hong, Ping; Peng, Sijia; Zou, Tong; Yang, Yue; Xing, Xinxin; Wang, Zhezhe; Zhao, Rongjun; Yan, Zhiyong; Wang, Yude
Abstract: Co(OH)2 @FeCo2 O4 nanocomposite was successfully synthesized via a facile one-step hydrothermal reaction without thermal treatment. The structure and chemical composition of as-synthesized Co(OH)2 @FeCo2 O4 was characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), and X-ray photoelectron spectroscopy (XPS), respectively. The results show the FeCo2 O4 nanosheets are covered with the Co(OH)2 nanoparticles and the BET show the nanocomposite possess the mesoporous structure with specific surface area and total pore volume are 93.071 m 2 g −1 and 0.37 cm 3 g −1, respectively. In addition, the electrochemical performances were investigated in a three-electrode system to evaluate the material. The as-synthesized Co(OH)2 @FeCo2 O4 nanocomposite exhibits a high specific capacitance of 1173.43 F g −1 at 1 A g −1 and remarkable cycling stability with 95.4% capacitance retention after 5000 cycles. The results show the higher capacitance and longer cycle performance, compared with the Co(OH)2 and FeCo2 O4, respectively. This remarkable electrochemical performances were mainly due to mesoporous structure and the synergistic effect of Co(OH)2 and FeCo2 O4 . It means that this nanostructure Co(OH)2 @FeCo2 O4 synthesized by this simple and cost-effective method would have more hopeful prospects in energy storage applications. Graphical abstract: Co(OH)2 @FeCo2 O4 nanocomposite applied as electrode of supercapacitor shows an impressive enhancement of the performance including the areal capacitance and cycling stability.Image 1